Rehabilitation interventions - Turk, Margaret A.; Mudrick, Nancy R.; Sage eBooks (Los Angeles, California : SAGE, 2012)
This volume in 'The SAGE Reference Series on Disability' explores ethical, legal, and policy issues of people with disabilities, and is one of eight volumes in the cross-disciplinary and issues-based series, which examines topics central to the lives of individuals with disabilities and their families.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: People with disabilities -- Rehabilitation; People with disabilities -- Services for; People with disabilities -- Functional assessment; Electronic books